Kebinekaan Kebinekaan dan Mini Talkshow di Metro TV - Rona Marina Nisaasari (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
Abstract This article discussed about diversity and the production management of an annual event program in order to welcome the Christmas and New Year 2018 – 2019. The program called the Christmas and New Year Pre Event program 2018 – 2019 with the theme of